Sinkronisasi Kewenangan Regulasi Pemerintah Kabupaten/Kota sebagai Model Implementasi Kebijakan Ekonomi Nasional yang Mendukung Iklim Investasi di Daerah - F.C. Susila Adiyanta (Administrative Law and Governance Journal, 2019)
Abstract This study aims to Synchronize the Authority of Regency / City Government Regulations as a Model of the Implementation of National Economic Policies that Support the Investment Climate in the Region. By using a statute approach and empirical approach, this research is carried out to identify regulatory authorities and solutions to problems in regional regulations that are not conducive to national policies on investment in the region. The results of the study obtained conclusions: a) the characteristics and problems of regional regulations in supporting the implementation of investment policies in regions categorized into general and specific characteristics. General characteristics include legal products that have juridical problems, substance, and legal principles, while special characteristics are problems related to supporting legal products that can affect the business climate and competitiveness of investment, spatial planning, and regional institutions; b) Measures for governance of regional regulations to support the implementation of national economic policies that are conducive to investment for investment require planning, design, and preparation of comprehensive regional regulations by synchronizing the content of regional regulations involving all elements in the region, namely: executive institutions , legislative, business actors, and the community. Some recommendations from the results of this study are: a) local governments need to increase institutional capacity, innovation, and public services; b) the existence of experts who can be a reference in the design and preparation of regional regulations that are conducive to the investment climate and business competitiveness; c) in the preparation and design of regional regulations it is necessary to further increase access to public participation. Keywords: National Economic Policy, Regional Regulations, Investment Abstrak Penelitian ini bertujuan untuk Sinkronisasi Kewenangan Regulasi Pemerintah Kabupaten/Kota sebagai Model Implementasi Kebijakan Ekonomi Nasionalyang Mendukung Iklim Investasi di Daerah. Dengan menggunakan pendekatan perundang-undangan (statute approach) dan empiris (empirical approach), penelitian ini dilakukan untuk mengidentifikasi kewenangan regulasi dan model solusi permasalahan peraturan daerah yang tidak kondusif bagi kebijakan nasional tentang investasi di daerah.  Hasil kajian diperoleh kesimpulan : a) karakteristik dan kebermasalahan peraturan daerah dalam mendukung implementasi kebijakan investasi di daerah kategorikan ke dalam karakteristik umum dan khusus. Karakteristik umum meliputi produk-produk hukum yang mempunyai kebermasalahan yuridis, substansi, dan prinsip-prinsip hukum, sedangkan karakteristik khusus adalah kebermasalahan yang berkaitan dengan produk-produk hukum pendukung yang dapat mempengaruhi iklim usaha dan daya saing investasi, tata ruang, dan kelembagaan daerah; b) Langkah-langkah solutif tata kelola peraturan daerah untuk mendukung implementasi kebijakan ekonomi nasional yang kondusif bagi investasi  bagi investasi memeerlukan perencanaan, perancangan, dan penyusunan peraturan derah yang komprehensif dengan sinkronisasi materi muatan peraturan daerah yang melibatkan semua elemen di daerah, yaitu: lembaga eksekutif, legislatif, pelaku usaha, dan masyarakat. Beberapa rekomendasi dari hasil penelitian ini adalah : a) pemerintah daerah perlu meningkatkan kapasitas kelembagaan, inovasi, dan pelayanan publik; b) adanya tenaga ahli yang dapat menjadi rujukan dalam perancangan dan penyusunan peraturan daerah yang kondusif bagi iklim investasi dan daya saing usaha; c) dalam penyusunan dan perancangan peraturan derah perlu lebih meningkatkan akses partisipasi publik. Kata kunci: Kebijakan Ekonomi Nasional, Peraturan Daerah,  Investasi